2018
DOI: 10.1149/2.0341803jes
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion Inhibition of Aluminum Alloy AA6063-T5 by Vanadates: Microstructure Characterization and Corrosion Analysis

Abstract: Corrosion inhibition of aluminum alloy AA6063-T5 by vanadates (NaVO 3 ) in 0.05 M NaCl solution has been investigated by electrochemical and weight loss measurements, and associated with microstructure and Volta potential data. X-ray diffraction, scanning electron microscopy, and energy dispersive spectroscopy analyses confirmed the presence of micrometer-sized Fe-rich Al 4.01 MnSi 0.74 , Al 1.69 Mg 4 Zn 2.31 , and FeAl 3 intermetallic phases (IMPs) and nanometer-sized CuAl 2 , ZnAl 2 , and Mg 2 Si precipitate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 59 publications
0
31
0
11
Order By: Relevance
“…Coatings 2020, 10, 226 15 of 60 15% for AlO6. The roles that surface coordination plays in precipitation and dissolution of mineral phases had been discussed elsewhere [83][84][85][86].…”
Section: Structure and Composition Of Anodized Oxide Layer On Anodizementioning
confidence: 99%
See 2 more Smart Citations
“…Coatings 2020, 10, 226 15 of 60 15% for AlO6. The roles that surface coordination plays in precipitation and dissolution of mineral phases had been discussed elsewhere [83][84][85][86].…”
Section: Structure and Composition Of Anodized Oxide Layer On Anodizementioning
confidence: 99%
“…Madden and Scully [210] had described in more detail how this might be possible with permanganate anion. This possibility is strengthened by the reported inhibitive effects of permanganates [210][211][212][213][214], tungstates [215][216][217], molybdates [67,152,[211][212][213][214][215][216][217][218][219][220], and vanadates [221][222][223][224][225][226][227] on aluminum corrosion and enhanced corrosion resistance of the anodic films formed on aluminum alloys. These anions are known to form "alumino-oxy" compounds with aluminum like chromate anion such as; aluminum tungstate [228][229][230], aluminum molybdate [231][232][233][234], aluminum permanganate [235,236], and aluminum vanadate [237].…”
Section: Candidate Chromate Alternativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Corrosion studies were carried out in three media: 0.5 M NaCl, 0.5 M H 2 SO 4 , and 2 M NaOH solutions at room temperature (≈ 20°C‐22°C). Concentrations of these media were selected based on the literature review . Potentiodynamic polarization scans and electrochemical impedance spectroscopy (EIS) tests were performed using an Autolab PGSTAT 302 N potentiostat‐galvanostat (Methrom Autolab, The Netherlands) in a three‐electrode glass cell.…”
Section: Methodsmentioning
confidence: 99%
“…They reported that the addition of Zn and Mg to AlSi-based coatings increases the corrosion resistance in chloride-containing environments. From a practical and an industrial point of view, however, lower concentrations of Zn and Mg, which have low melting temperatures, are favored to avoid the liquid metal embrittlement (LME) phenomenon [ 19 ] and localized corrosion attack caused by the selective dissolution of these alloying elements [ 6 , 20 ].…”
Section: Introductionmentioning
confidence: 99%